Actividad antibacteriana del extracto etanólico de Lessonia nigrescens Bory (Aracanto) frente a Staphylococcus aureus 6538 y Escherichia coli ATCC 8739 - Bocanegra Esteban, Jeans Darci (2019)
The antibacterial activity of the ethanolic extract of the marine macroalga Lessonia nigrescens was evaluated against typified bacterial strains. The obtaining of the extract was done through the maceration technique, to determine the presence of metabolites phytochemical screening it was made, and the antimicrobial activity was evaluated by means of diffusion technique on Kirby Bauer agar. The results showed that L. nigrescens against Staphylococcus aureus ATCC 6538 shows an average inhibition halo of 8.52mm and to Escherichia coliATCC 8739 shows no activity; the phytochemical creening detected the presence of various compounds, including phenolic compounds, sterols, tannins and alkaloids. Concluding that the ethanolic extract of L. nigrescens Bory presented antimicrobial activity only against Staphylococcus aureusATCC 6538, attributing said property to the metabolites found.